Incidence of Fall and its Associated Factor: A Single Centre Experience - Lim, Bee Chiu; Mahmud, Fatihah; Abdullah, Bunyamin; Badrul Hisham, Muhammad Hazrul; Nalalingam, Shanti; Mohamad Nor, Fariz Safhan (IIUM Medical Journal Malaysia, 2024)
INTRODUCTION: Patient falls during hospitalisation can cause catastrophic injuries and remain one of the major patient-safety issues faced by hospitals. This study was designed to determine the inpatient falls rate and the association between fall-related injury and sociodemographic variables. MATERIALS AND METHODS: A retrospective record review was conducted for a one-time inpatient fall in a single centre between January 2017 and December 2019. Pearson chi-square or Fisher’s exact test were performed to assess association between the categorical variables. RESULTS: There were 44 inpatient falls who fell one time between January 2017 and December 2019. The inpatients fall rate was 3.0 per 10000 patient-days from 2017 to 2019. Overall, the patients who fell experienced an injury (n=24, 55%). There was no significant difference between age group, gender, time of fall, assisted type, history of fall, fall risk assessment, mental status, the department involved, and injurious fall outcome. CONCLUSION: Our study showed a low incidence of fall rate per 10000 patient-days for 2017-2019. More than half of the fallers experienced an injurious fall. The highest fall rate was noted in the surgical based departments. However, there was no significant difference between injurious fall outcomes and sociodemographic variables. Risk assessments and management strategies should focus on education, particularly bed safety.